The Relationship between Parenting Style Implementation and the Occurrence of Stress Among Strawberry Generation Adolescents in the Makassar Region - Afifah Azzahra; Arlina Wiyata Gama; Ulfah Rimayanti; Veraferial Mukhtar; Nadyah Haruna; Siti Aisyah Kara (JURNAL IMPLEMENTA HUSADA, 2026)
Introduction: Stress is a common psychological phenomenon experienced by adolescents and may have either positive (eustress) or negative (distress) effects on mental health and psychosocial development. Parenting styles play an important role in shaping adolescents’ ability to understand and manage stress. Objective: This study aimed to analyze the relationship between parenting styles and the occurrence of stress among adolescents. Methods: This study employed a quantitative design with a cross-sectional approach involving 85 students from SMA Islam Athirah Bukit Baruga, Makassar City. Stress levels were measured using the Perceived Stress Scale (PSS) and the Adolescent Distress–Eustress Scale (ADES), while parenting styles were assessed using the Parental Authority Questionnaire. Data analysis was conducted using univariate and bivariate analyses with the Chi-square test. Results: The results showed that most respondents experienced moderate stress levels, and the majority of adolescents experienced positive stress (eustress). Authoritative parenting was predominantly found among adolescents experiencing positive stress, whereas authoritarian and permissive parenting styles were more dominant among adolescents experiencing negative stress. Statistical analysis revealed a significant relationship between parenting styles and stress occurrence among adolescents (p = 0.044; p 0.05). Conclusion: Balanced parenting characterized by appropriate control and warmth plays an important role in promoting positive stress (eustress) among adolescents.